The Effectiveness of Child Protection Through Marriage Dispensation Policy in Maslāḥah Perspective (American Journal of Society and Law, 2023)
Maslāḥah means interests and benefits, which, when used together with the word mursalah, means unlimited, unrestricted, or freely decided interests. The Maslāḥah mursalah method emerges as a fundamental understanding of the concept that shari’ah is intended for the benefit of the community and serves to provide benefits and prevent harm. This research is descriptive and qualitative, with a normative theological approach, normative juridical, and empirical juridical. Research data sources include the Watampone Religious Court, the Ministry of Religion of Bone Regency, and the Office of Women’s Empowerment and Child Protection in Bone Regency. The Watampone Religious Court carries out child protection through discretionary restrictions on accepting applications for marriage dispensation, which must be with a recommendation from the Office of Women’s Empowerment and Child Protection in Bone Regency (proven pregnant) as an indication of “very urgent”. This policy is contrary to the culture of the people of Bone; and concerning the “Best Interests of the Child”, the point is included in the category of al-Maṣlaḥah al-Hajiyah and al-Maṣlaḥah al-Mursalah.